NILAI EKONOMI REKREASI WISATA ALAM AIK NYET, KPHL RINJANI BARAT: APLIKASI METODE BIAYA PERJALANAN - Kresno Agus Hendarto; Rubangi Al Hasan; Yumantoko Yumantoko; Ahmad Nur; Kuncoro Ariawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
Good knowledge about the economic value of a particular tourist destination is the primary fundamental in effective management policy formulation. In 2015, the Aik Nyet Nature Tourism (Aik Nyet), which covers an area of approximately 9.4 ha, is one of the tourist destinations planned to receive donation from the Provincial Government of West Nusa Tenggara (NTB) for the improvement and development of the facilities and infrastructures as well as the capacity building for the people around the tourist location. Using the travel cost methods this study estimates the economic benefits of the recreational value in the Aik Nyet before the realization of the donation from the Provincial Government of West Nusa Tenggara. Consumers’ surplus per individual per visit is estimated using the data collected from the survey in the tourist location. Using poisson regression, the total travel costs (that includes such variables as transportation cost, consumption cost, and location entrance cost) are considered in the study to explain the frequency of individual’s visit to the tourist location. The results of the study suggest that the economic recreational value generated by the Aik Nyet before the realization of the government’s financial support is approximately Rp. 9.333.627, 7 per year.